Mengubah Sampah Menjadi Solusi: Implementasi Ecobrick dalam Program KKN Berbasis Edukasi Lingkungan - Erpita Yanti; Aulia Khalifatul Ummah; Nadilla Putri E; Prima Aditya; Sheila Ivana Khalishah; Verrel Andrean Pradipa (BADAN PENERBIT STIEPARI PRESS, 2025)
The Community Service Program (KKN) of Universitas Negeri Padang (UNP) in Nagari Bukik Limbuku focuses on addressing the serious plastic waste problem caused by population density and economic activities. With an estimated 5–13 million tons of plastic polluting the oceans each year, waste management has become an urgent issue, leading to environmental pollution, declining water quality, flood risks, and health problems. UNP students introduced an innovative solution through ecobricks, which transform plastic waste into solid, reusable materials. This initiative was realized in the construction of the “Bukik Limbuku” village name installation made from ecobricks, accompanied by community outreach and environmental education. The program began with an ecobrick demonstration at SD 01 Nagari Bukik Limbuku on June 20, 2025, followed by intensive training sessions until July 17, 2025. The results showed not only increased environmental awareness but also equipped the community with practical skills, highlighting the university’s role in sustainable community empowerment.